Design and analysis of a novel active screw-drive pipe robot. (October 2018) - Li, Pengs; Tang, Ming; Lyu, Congyi; Fang, Mengjun; Duan, Xingguang; Liu, Yunhui
This study proposes a novel active screw-drive in-pipe robot that can adapt the circular-type and square-type pipe structure. The pipe robot is composed of four driving units and a wall-pressing suspension mechanism. Each driving unit contains a motor, a transmission train, and an electromagnetic brake, which is for switching the motion transmission route. DC motors drive the helical wheels, and the incline angle of the helical wheels can be adjusted by using the electromagnetic brake. The wheels of the driving unit exhibit rolling and steering motion. Thus, the robot is capable of translation movements, rotation movements, and screw motions with respect to the axis of the pipe according to the different positions of the helical wheels. The robot can avoid obstacles by using the rotation and screw modes. Moreover, the wall-pressing mechanism is analyzed and modified, and a criteria for entering a reduction pipe reducer are derived for the double scissor-like suspension mechanism. We also analyze the robot motion in curved pipes in two typical postures. The simulation experiments reveal the relationship between the translation and rotation motion of the robot and indicates that the steering angle of the wheels can be regarded as a regulator to adjust the movement speed of the robot aside from tuning the posture of the robot. Elbow experiments are conducted to verify the effectiveness of the motion strategy. The robot can be adapted for both circular and square tube pipes without any change in its structure due to the special configuration.